1998
DOI: 10.1093/oxfordjournals.jbchem.a021921
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of a Marine Bacterial  -Galactoside  2,6-Sialyltransferase Gene from Photobacterium damsela JT0160

Abstract: Sialyltransferase 0160, a bacterial sialyltransferase which catalyzes the incorporation of NeuAc from CMP-NeuAc into the galactose residue of the carbohydrate chain at position 6, is produced by Photobacterium damsela JT0160. The gene coding for sialyltransferase 0160 (bst) was cloned, sequenced, and expressed in Escherichia coli. The sialyltransferase 0160 gene contains an open reading frame of 2,028 base pairs encoding a protein of 675 amino acid residues. The deduced amino acid sequence of sialyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 35 publications
0
56
1
Order By: Relevance
“…This was performed in a 100-l reaction mixture containing 100 ng of genomic DNA as template, 300 nmol of primers, 200 mM dNTPs, 50 mM KCl, 10 mM Tris-HCl (pH 8.3), 2 mM MgCl 2 , 0.01% gelatin, 0.1% Triton X-100, and a mixture of both Taq DNA polymerase and pfu DNA polymerase (1 unit of each). Two primers, the forward primer with internal BamHI (underlined) site (5Ј-ATATTGGATCC)ATATTTGAT-GCTAGTTTA-3Ј; nucleotides [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and a reverse primer with EcoRI site, (5Ј-GGCGCGAATTCTTACTCCCCCAAGAAAA-3Ј; nucleotides 1230 -1214) designed based on the previously published sequence (14) were used for PCR using the following conditions: 94°C, 1 min; 50°C, 1 min; and 72°C, 2 min for 35 cycles. Agarose gel analysis of the product showed the presence of one major band with the expected size of about 1.2 kilobases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was performed in a 100-l reaction mixture containing 100 ng of genomic DNA as template, 300 nmol of primers, 200 mM dNTPs, 50 mM KCl, 10 mM Tris-HCl (pH 8.3), 2 mM MgCl 2 , 0.01% gelatin, 0.1% Triton X-100, and a mixture of both Taq DNA polymerase and pfu DNA polymerase (1 unit of each). Two primers, the forward primer with internal BamHI (underlined) site (5Ј-ATATTGGATCC)ATATTTGAT-GCTAGTTTA-3Ј; nucleotides [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and a reverse primer with EcoRI site, (5Ј-GGCGCGAATTCTTACTCCCCCAAGAAAA-3Ј; nucleotides 1230 -1214) designed based on the previously published sequence (14) were used for PCR using the following conditions: 94°C, 1 min; 50°C, 1 min; and 72°C, 2 min for 35 cycles. Agarose gel analysis of the product showed the presence of one major band with the expected size of about 1.2 kilobases.…”
Section: Methodsmentioning
confidence: 99%
“…The sialyltransferases that catalyze the addition of sialic acid to form such diverse carbohydrate recognition molecules fall into at least two families. While 13 clones have been obtained from mammalian systems (12), only 4 have been cloned from bacterial systems to date (13)(14)(15)(16). Recent cloning of both mammalian and bacterial sialyltransferases showed that these two gene families evolved differently.…”
mentioning
confidence: 99%
“…The flexible donor and acceptor substrate specificities of the enzyme were described and the enzyme was applied in the synthesis of α2,6-linked sialosides and glycopeptides (Yamamoto et al 1998a;Yu et al 2006;Yamamoto et al 1998b;Kajihara et al 1996;Teo et al 2005;Yamamoto et al 1996;Endo et al 2001). Pd2,6ST shares amino acid sequence homology with a multifunctional Pasteurella multocida sialyltransferase PmST1 encoded by gene Pm0188 (GenBank accession numbers: AAY89061, AAK02272) (Yu et al 2005), a Haemophilus ducreyi α2,3-sialyltransferase encoded by gene Hd0053 (GenBank accession number: AAP95068) (Li et al 2007), a Photobacterium phosphoreum α2,3-sialyltransferase encoded by gene pst3-467 (GenBank accession number: BAF63530) , and a Photobacterium leiognathi α2,6-sialyltransferase ).…”
Section: Introductionmentioning
confidence: 99%
“…This PhoU domain has been proven to be unrelated to the sialyltransferase activity of Pd2,6ST (Yamamoto et al 1998a;Yu et al 2006). The lipobox-containing Nterminal 15 amino acids deleted in the purified native Pd2,6ST enzyme ) may function as a signal sequence.…”
Section: Introductionmentioning
confidence: 99%
“…In general, bacterial STases are also important for the enzymatic modification of glycoconjugates and the enzymatic synthesis of glycans because they are more stable and productive than mammalian enzymes. Since 2,3-STase was first cloned from Neisseria meningitidis and N. gonorrhoeae (Gilbert et al, 1996), bacterial STases have been cloned from several microorganisms (Gilbert et al, 2000;Yamamoto et al, 1998;Bozue et al, 1999;Shen et al, 1999). To date, the crystal structures of three bacterial STases have been reported: the bifunctional STase CstII from Campylobacter jejuni (Chiu et al, 2004), the 2,3-STase CstI from C. jejuni (Chiu et al, 2007) and the multifunctional STase Á24PmST1 from Pasteurella multocida (Ni et al, 2006(Ni et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%